Diagnostic accuracy of dental pulse oximeter with customized sensor holder, thermal test and electric pulp test for the evaluation of pulp vitality: an in vivo study - Janani, Krishnamachari; Palanivelu, Ajitha; Sandhya, Raghu (Brazilian Dental Science, 2020)
Background: the efficiency of the diagnostic aids plays an important role in the treatment plan. This study aims to assess the diagnostic accuracy of dental pulse oximeter with a customized sensor holder, thermal test and electric pulp tester in assessing the actual pulp status and to evaluate the oxygen saturation level in control healthy teeth, non-vital and teeth with irreversible pulpitis. Material and methods: thirty-seven single canal teeth requiring endodontic therapy were included in the study. The selected teeth were tested with dental pulse oximeter, electric pulp test, cold spray, and heated gutta percha stick. Between each test a time lag of 2 minutes was allowed for the central sensitization to occur.  Three blinded operators were involved in the study. The actual status of the pulp was evaluated after the initiation of endodontic treatment. To assess the actual pulp status direct visual examination of access cavity as performed. The data was statistically analysed using (ANOVA) Analysis of Variance and Post-hoc Tukey test. Results: sensitivity of pulse oximeter, heat test, cold and electric pulp test, was 100, 25, 50, and 12, respectively. The specificity of these tests was 100, 72 81, and 77, respectively. The ANOVA showed that there was statistical difference between all the groups (p=0.0005). Post-Hoc Tukey revealed that there was statistical difference among all the groups, nonvital group (p=0.0005), control group (p=0.01) and for irreversible pulpitis (p=0.01). The overall diagnostic accuracy of pulse oximeter was 100% followed by cold test 66%, heat test to be 49% and electric pulp test to be 45%. Conclusion: the custom-made holder used in the present study aided in providing accurate response for pulp vitality testing. In this study the diagnostic accuracy was high with dental pulse oximeter followed by cold, heat and the least was electric pulp tester in different pulpal conditions.KEYWORDS Cold test; Heat test; Oxygen saturation; Pulse oximeter; Vitality tests.